2022
DOI: 10.34172/jlms.2022.09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiotherapy in Combination With Irinotecan and 17-AAG on Bcl-2 and Caspase 3 Gene Expression in Colorectal Cancer Cells

Abstract: Introduction: In this study, the cytotoxic and anti-cancer effects of Irinotecan as a conventional chemotherapeutic agent compared to 17-(allyl amino)-17-demethoxygeldanamycin (17-AAG) as possible radiosensitizers in the HCT-116 cell line were investigated. Methods: HCT-116 cells were treated with various concentrations of irinotecan and 17-AAG and also irradiated with a 2-Gy of X-ray radiation. Then, the cell viability was examined by a water-soluble tetrazolium-1 assay after 24 hours. For single therapies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
2
2
0
Order By: Relevance
“…The HT-29 chells we used are also characterized by a p53 mutation. Since we found no effect in irradiated cells treated with oxaliplatin and 5-FU, our results correspond to those of Magné et al With regard to irinotecan, Ebrahimpour [59] demonstrated a significant reduction in the MTT-assay in HCT-116 cells 24 h after the treatment with irradiation or irinotecan. In our study, there was no difference at this time point, possibly due to different cell lines.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The HT-29 chells we used are also characterized by a p53 mutation. Since we found no effect in irradiated cells treated with oxaliplatin and 5-FU, our results correspond to those of Magné et al With regard to irinotecan, Ebrahimpour [59] demonstrated a significant reduction in the MTT-assay in HCT-116 cells 24 h after the treatment with irradiation or irinotecan. In our study, there was no difference at this time point, possibly due to different cell lines.…”
Section: Discussionsupporting
confidence: 91%
“…The radiosensitive activity of oxaliplatin was first described by Blackstock et al in 1999 [ 43 ] in an abstract of the 41st annual ASTRO meeting, and, in the last two decades that followed, several preclinical studies investigated its cytotoxic effects in combination with irradiation but not on human colorectal cancer cells [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Similar, preclinical studies reported on the cytotoxic effects of irinotecan [ 17 ] on colorectal cancer [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ] or non-colorectal [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ] cancer cells. The aim of these studies was to determine the influence of oxaliplatin [ 44 , 46 , 47 , 51 , 52 , 53 , 54 , 55 , 57 ] and irinotecan [ 63 , 64 , 65 , 66 ] on cellular pathways, cell cycle and mechanisms of drug resistance or to describe mechanisms of radiosensitization and radioresistance with oxaliplatin [ 45 , 48 , …”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations